Culture as weapon the art of influence in everyday life - Thompson, Nato 1972- (Melville House, 2017)
"One of the country's leading activist curators explores how corporations and governments have used art and culture to mystify and manipulate us. The production of culture was once the domain of artists, but beginning in the early 1900s, the emerging fields of public relations, advertising and marketing transformed the way the powerful communicate with the rest of us. A century later, the tools are more sophisticated than ever, the onslaught more relentless. In Culture as Weapon, acclaimed curator and critic Nato Thompson reveals how institutions use art and culture to ensure profits and constrain dissent...and shows us that there are alternatives. An eye-opening account of the way advertising, media, and politics work today, Culture as Weapon offers a radically new way of looking at our world"...
Includes bibliographical references
Keywords: Geschichte 2000-2017; SOCIAL SCIENCE / Anthropology / Cultural; POLITICAL SCIENCE / Public Policy / Cultural Policy; BUSINESS & ECONOMICS / Advertising & Promotion; Geschichte; Politik; Wirtschaft; Arts and society -- History -- 21st century; Arts -- Political aspects -- History -- 21st century; Social influence; Mass media and culture; Massenmedien; Manipulation; Kommerzialisierung; Kultur